Electrostatics explains the shift in VDAC gating with salt activity gradient. - Levadny, Victor (2002)
We have analyzed voltage-dependent anion-selective channel (VDAC) gating on the assumption that the states occupied by the channel are determined mainly by their electrostatic energy. The voltage dependence of VDAC gating both in the presence and in the absence of a salt activity gradient was explained just by invoking electrostatic interactions. A model describing this energy in the main VDAC states has been developed. On the basis of the model, we have considered how external factors cause the redistribution of the channels among their conformational states. We propose that there is a difference in the electrostatic interaction between the voltage sensor and fixed charge within the channel when the former is located in the cis side of membrane as opposed to the trans. This could be the main cause of the shift in the probability curve. The theory describes satisfactorily the experimental data (Zizi et al., Biophys. J. 1998. 75:704-713) and explains some peculiarities of VDAC gating. The asymmetry of the probability curve was related to the apparent location of the VDAC voltage sensor in the open state. By analyzing published experimental data, we concluded that this apparent location is influenced by the diffusion potential. Also discussed is the possibility that VDAC gating at high voltage may be better described by assuming that the mobile charge consists of two parts that have to overcome different energetic barriers in the channel-closing process.